Globalising education: how far is the 'TEACH' model of initial teacher education transferable across North and South contexts? - Elliott, J.M. (2017)
Teach for All is an umbrella organisation developed by the founders of Teach for America and Teach First. Operating through sister organisations in Africa, Asia, Australia, Europe, North America and South America, Teach for All promises to develop solutions to educational problems in diverse settings through training teachers according to common principles to work in schools in areas of disadvantage. For the first time, therefore, there exists a single international organisation offering a model of teacher education which claims to be transferable to any context in the world. This study, through a focus on Teach South Africa in the Global South and the UK’s Teach First in the Global North, seeks to examine these claims. In particular it investigates the extent to which the teacher training model has been transferred, established and embedded in what are culturally, economically, politically and historically very different nation states. CEOs, middle managers and teachers of the respective organisations were interviewed and Teach for All, Teach First and Teach South Africa web-sites were analysed, in order to gain an understanding of how the principles, aims and ethos are embodied within the organisation’s different settings. I argue that, while pervasive neoliberal ideologies along with a specific organisational discourse combine to create a set of circumstances in which Teach for All believes it can establish 'country proof’ sister organisations anywhere in the world, the North in fact maintains and strengthens its privilege and power base in these relationships and they are not necessarily supportive of teacher development needs in the Global South.